Trust, Trustworthiness, and Information Sharing in Supply Chains Bridging China and the United States - Özer, Özalp; Zheng, Yanchong; Ren, Yufei (Management Science, 2014)
Whether and how trust and trustworthiness differ between a collectivist society, e.g., China, and an individualistic one, e.g., the United States, generates much ongoing scientific debate and bears significant practical values for managing cross-country transactions. We experimentally investigate how supply chain members' countries of origin—China versus the United States—affect trust, trustworthiness, and strategic information sharing behavior in a cross-country supply chain. We consider a two-tier supply chain in which the upstream supplier solicits demand forecast information from the retailer to plan production; but the retailer has an incentive to manipulate her forecast to ensure abundant supply. The levels of trust and trustworthiness in the supply chain and supplier's capability to determine the optimal production quantity affect the efficacy of forecast sharing and the resulting profits. We develop an experimental design to disentangle these three aspects and to allow for real-time interactions between geographically distant and culturally heterogeneous participants. We observe that, when there is no prospect for long-term interactions, our Chinese participants consistently exhibit lower spontaneous trust and trustworthiness than their U.S. counterparts do. We quantify the differences in trust and trustworthiness between the two countries, and the resulting impact on supply chain efficiency. We also show that Chinese individuals exhibit higher spontaneous trust toward U.S. partners than Chinese ones, primarily because they perceive that individuals from the United States are more trusting and trustworthy in general. This positive perception toward U.S. people is indeed consistent with the U.S. participants' behavior in forecast sharing. In addition, we quantify that a Chinese supply chain enjoys a larger efficiency gain from repeated interactions than a U.S. one does, as the prospect of building a long-term relationship successfully sustains trust and trustworthiness by Chinese partners. We advocate that companies can reinforce the positive perception of westerners held by the Chinese population and commit to long-term relationships to encourage trust by Chinese partners. Finally, we also observe that both populations exhibit similar pull-to-center bias when solving a decision problem under uncertainty (i.e., the newsvendor problem). Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2014.1905 . This paper was accepted by Yossi Aviv, operations management.